Profile of the Refereeing Division of the Provincial Board of PBSI Gorontalo 2023 - Iwan Fataha; Dewi, Ratna; Ardin Abdul Gani; Samin, Giofandi; Ramadan, Gilang (Jurnal Ilmiah Sport Coaching and Education, 2023)
ABSTRAK Wasit merupakan faktor yang sangat menentukan jalannya pertandingan sesuai aturan, jadi memang seorang wasit bulutangkis harus mengetahui berbagai hal terkait aturan bulutangkis yang benar dan segala fasilitas yang mendukung pertandingan, sarana prasarana pertandingan sertahal-hal yang terkait ke pertandingan. Metode dalam penelitian ini adalah metode survey deskriptif kualitatif. Hasil dari penelitian ini adalah data seluruh wasit di PBSI Gorontalo. Kesimpulan dari penelitian ini adalah semua wasit yang ada di PBSI Provinsi Gorontalo memiliki pengalaman dalam memimpin banyak pertandingan dan semuanya memiliki lisensi baik kota maupun provinsi. Kata Kunci: Wasit Bulu Tangkis ABSTRACT The referee is a very decisive factor for the course of the match according to the rules, so indeed a badminton referee must know various things related to the correct badminton rules and all the facilities that support the match, the match infrastructure as well as matters related to the match. The method in this research is a descriptive qualitative survey method. The results of this study are data on all referees in PBSI Gorontalo. The conclusion of this study is that all of the referees in the PBSI Gorontalo provincial management have experience in leading many matches and all of them have licenses for both the city and the province. Keywords: Badminton Referee